Hormonal study of patients infected with rheumatoid arthritis in Babylon province - Ihsan R.I.; Mohammad R. ALJibor (Al-Qadisiyah Journal of Pure Science, 2017)
This study was designed to investigate some hormonal changes for patients who are infected by rheumatoid arthritis ,They are coming to Marjan hospital in Babylon city from period December 2011 to June 2012. It has taken the information of patients which included the age, gender, and the period of the illness. Their number has reached to (80) patients (60) of them are females and (20) of them are males, in comparison with healthy people who their number reached to (30) .(22) of them are females and (8) of them are males. After taking a special information the blood samples were taken 5ML and serum was isolated and testes were carried out which included the level of thyroxin T4 and triiodothyronine T3 in addition to TSH. The results of this study showed:Significant decrease (P<0.05) in T4,T3 and significant increase (P<0.05) TSH for people who suffering from rheumatoid arthritis in comparison with control group. Also, this study included investigate the relationship between studied parameters and some factors (gender, age, and the period of illness) for infected people in comparison with uninfected people. It has concluded from this study that the infected female which are suffered from negative changes for the studied parameters in comparison with males. In addition the long age and period of illness have negative effect upon the studied parameters in comparison with control group.